Outcomes Following a Moderately Hypofractionated Adjuvant Radiation (START B Type) Schedule for Breast Cancer in an Unscreened Non-Caucasian Population. Issue 10 (October 2016) - Chatterjee, S.; Arunsingh, M.; Agrawal, S.; Dabkara, D.; Mahata, A.; Arun, I.; Shrimali, R.K.; Achari, R.; Mallick, I.; Ahmed, R.
Abstract: Aims: Breast cancer is the most common cancer in women. Western data have confirmed hypofractionated radiation therapy to be safe and effective in the adjuvant radiation therapy of breast cancers. We report the disease-related outcomes in a non-Caucasian, unscreened population treated with hypofractionated radiation. Materials and methods: Unselected case notes of patients presenting to a tertiary cancer centre between June 2011 and December 2013 were reviewed from the electronic hospital case records. Patients with a diagnosis of non-metastatic invasive non-sarcomatous breast cancer were identified. Demographic information, oestrogen receptor (ER), progesterone receptor (PR), HER2 status, pathological tumour, nodal stage at diagnosis and outcomes of treatment, including systemic therapies, surgery and hypofractionated radiation, were documented. Local recurrence rates, disease-free survival (DFS) and overall survival were calculated. Results: Overall 925 patents were identified, median age 53.0 years (interquartile range 45–61), 330 of whom had neoadjuvant chemotherapy. The median follow-up time was 22.6 months and 23.5 months for overall and neoadjuvant chemotherapy groups, respectively. ER, PR and HER2 status was available in 788 patients, 77.2% of whom were ER/PR positive, 14.7% had triple negative disease, while 9.5% were HER2 rich. Overall, 34.2% (113 patients) underwent breast conservation surgery; 744 (80.4%) patients were treated with systemic chemotherapy and 878 (94.9%) patients received adjuvant radiation therapy, of whom 407 (44.0%) received supraclavicular-fossa radiotherapy. Overall survival, DFS and locoregional recurrence-free survival (LRRFS) for the overall group were 93%, 86.9% and 97.1%, respectively. LRRFS in the breast conservation surgery versus mastectomy groups were 99% versus 95.5% ( P  = 0.003), with more node-positive patients in the mastectomy group. Stage N0/1 had better LRRFS compared with N2/2 (99.1% versus 95.7%); 94.3% versus 82.3%; P  = 0.005, 0.000. Grade 3 (53.8%) tumours had worse overall survival compared with grade 1 or grade 2 disease (89.6% versus 100% and 96.4%; P  < 0.001) although the LRRFS was not significantly different between the groups (98.9% versus 97.8%; P  = 0.37). There was no difference in LRRFS based on molecular subtypes. Conclusion: Local recurrence rates following hypofractionated radiation in our population were comparable with those reported by the START trialists and were found to be safe in the medium term for patients irrespective of breast conservation surgery/mastectomy or radiotherapy to the supraclavicular field. Molecular group frequencies were comparable with Western populations but did not affect LRRFS. Highlights: ER/PR/HER2 status in Indian patients are similar to the reported Western literature. Hypofractionated radiation is safe and effective post mastectomy, BCS and for SCF RT. Locoregional recurrences were small and not affected by molecular type. Hypofractionated radiotherapy (START B type) is as safe as conventional radiotherapy.